Understanding Digital Marketing Strategy (International Journal of Scientific Research and Management (IJSRM), 2017)
Digital Marketing Strategy highlight on how the digital technologies make marketing more effective because they allow forindividual attention, better campaign management, and better product, marketing design, and execution. This article does not ignore thefundamental theories of marketing but emphasizes their usefulness in developing a response to the threats and opportunities created bythe Internet. It is easy to understand the flow diagram for developing the marketing strategies: understand customer needs, formulate astrategy, implement the strategy, and build trust with customers.